Алгоритмы эндодонтического лечения как фактор адекватного выбора и соблюдения медицинских технологий (LLC "Endo Press", 2020)
The results of efficiency of treatment of chronic apical periodontitis at the patients on a background of system osteoporosis in short-term and long-term supervision with use the peroral antibacterial therapy are resulted. The peak efficiency of application of osteotropic antibiotics is established in comparison with traditional antibacterial therapy or without it.